2009
DOI: 10.1021/cg9003593
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal−Electrochemical Synthesis of ZnO Nanorods

Abstract: Vertically aligned ZnO nanorods having high optical quality were prepared by a hydrothermal−electrochemical method. The nanorods were synthesized in a Zn(NO3)2 aqueous solution on Si substrates which were coated with a platinum conducting layer and a ZnO seed layer. They possessed a single-crystal würtzite structure and grew along the c-axis, perpendicular to the substrates. The height and diameter of the ZnO nanorods were up to ∼4.3 μm and 90−150 nm, respectively. The morphological, structural, and photolumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…It is clearly seen that the graphene sheets are decorated densely by small ZnO NPs. The diameter of ZnO NPs is estimated to be 5-10 nm and their crystalline structures can be observed clearly from the lattice fringes of the ZnO (0 0 2) plane with an interplanar spacing of approximately 0.52 nm and (1 0 0) plane with an interplanar distance of about 0.28 nm [44,45]. Additionally, the existence of Zn in the nanocomposite has been proved by the peaks of Zn in EDS data (Fig.…”
Section: Resultsmentioning
confidence: 81%
“…It is clearly seen that the graphene sheets are decorated densely by small ZnO NPs. The diameter of ZnO NPs is estimated to be 5-10 nm and their crystalline structures can be observed clearly from the lattice fringes of the ZnO (0 0 2) plane with an interplanar spacing of approximately 0.52 nm and (1 0 0) plane with an interplanar distance of about 0.28 nm [44,45]. Additionally, the existence of Zn in the nanocomposite has been proved by the peaks of Zn in EDS data (Fig.…”
Section: Resultsmentioning
confidence: 81%
“…The RGO nanosheets are curled and corrugated. The ZnO displays a hexagonal nanorod structure and its length and diameter decrease with the increase of RGO content in the composite, which implies that the presence of RGO inhibits the growth of ZnO nanorods [57]. It is observed that the RGO sheets with wrinkles and folds are decorated densely by the ZnO nanorods.…”
Section: Resultsmentioning
confidence: 97%
“…Moreover, during hydrothermal growth, residues from the organic precursor may be incorporated inside the ZnO NWs, which can be observed using XPS (Supplementary Figure S7 of the supporting information). [33][34][35][36] As the temperature rises above 450°C, these precursor residues decompose and evaporate, leaving the nanopores behind and thus forming internal pores. [34][35][36] To differentiate between the two types of pores, that is, the internal and external pores, a porous nanowire was rotated by tilting it inside the TEM (Figure 1c).…”
Section: Fabrication and Characterization Of The Visible-light Photodmentioning
confidence: 99%